Coexistence of Congenital Adrenal Hyperplasia and Autoimmune Addison's Disease - Aslaksen, Sigrid; Methlie, Paal; Vigeland, Magnus D.; Jøssang, Dag E.; Wolff, Anette B.; Sheng, Ying; Oftedal, Bergithe E.; Skinningsrud, Beate; Undlien, Dag E.; Selmer, Kaja K.; Husebye, Eystein S.; Bratland, Eirik (Frontiers in Endocrinology, 2019)
Background: Underlying causes of adrenal insufficiency include congenital adrenal hyperplasia (CAH) and autoimmune adrenocortical destruction leading to autoimmune Addison’s disease (AAD). Here, we report a patient with a homozygous stop-gain mutation in 3β-hydroxysteroid dehydrogenase type 2 (3βHSD2), in addition to impaired steroidogenesis due to AAD. Case report: Whole exome sequencing revealed an extremely rare homozygous nonsense mutation in exon 2 of the HSD3B2 gene, leading to a premature stop codon (NM_000198.3: c.15C>A, p.Cys5Ter) in a patient with AAD and premature ovarian insufficiency. Scrutiny of old medical records revealed that the patient was initially diagnosed with CAH with hyperandrogenism and severe salt-wasting shortly after birth. However, the current steroid profile show complete adrenal insufficiency including low production of pregnenolone, dehydroepiandrosterone (DHEA) and DHEA sulfate (DHEA-S), without signs of overtreatment with steroids. Conclusion: To the best of our knowledge, this is the first description of autoimmune adrenalitis in a patient with 3βHSD2 deficiency and suggests a possible association between AAD and inborn errors of the steroidogenesis.